1996
DOI: 10.3109/08990229609028909
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Detection and Pain Thresholds in Spinal Cord Injury Patients with and without Dysesthetic Pain, and in Chronic Low Back Pain Patients

Abstract: In an effort to understand the mechanisms involved in dysesthetic pain syndrome (DPS) in spinal cord injury (SCI) patients, four groups of 13 subjects each--SCI subjects with DPS, SCI subjects without pain, chronic low back pain subjects, and control subjects--were examined for sensory detection and pain thresholds at forearm, neck, and rostral trunk areas. Results indicated that the SCI pain group had significantly lower pain thresholds at all skin sites, compared to the SCI no-pain and chronic low back pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…Our preliminary observations of SCI patients are concordent with those of Song et al (1993) and Cohen et al (1996) suggesting that there are important alterations in cutaneous perceptual abilities far from the boundary between the anaesthetic and sentient regions of the body (SaddikiTraki et al, 1999); the threshold of light touch and the estimation of tactile stimulus intensity are altered over the entire anterior torso following a functionally complete SCI.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our preliminary observations of SCI patients are concordent with those of Song et al (1993) and Cohen et al (1996) suggesting that there are important alterations in cutaneous perceptual abilities far from the boundary between the anaesthetic and sentient regions of the body (SaddikiTraki et al, 1999); the threshold of light touch and the estimation of tactile stimulus intensity are altered over the entire anterior torso following a functionally complete SCI.…”
Section: Introductionsupporting
confidence: 82%
“…None reported symptoms compatible with intense chronic pain, but we did not administer a standard test such as the McGill Pain Questionnaire to obtain a more objective evaluation (M elzack and Loeser, 1978). Nevertheless, our patients did not report chronic pain and our touch thresholds are elevated as were those of patients without pain symptoms in the studies of Cohen et al (1996) andSong et al (1993).…”
Section: Differences In Tactile Sensitivity 399supporting
confidence: 43%
See 2 more Smart Citations
“…Several researchers have observed that in subjects with chronic pain, electrically evoked painless sensory and pain thresholds converge. 20,21 The present multicenter study was performed to characterize CPT and PTT values from CRPS subjects and healthy controls.…”
mentioning
confidence: 99%